Natural Selections : Selfish Altruists, Honest Liars, and Other Realities of Evolution. - Barash, David P. (Bellevue Literary Press, 2007)
If we are, in part, a product of our genes, can free will exist? Incisive and engaging, this indispensable tour of evolutionary biology runs the gamut of contemporary debates, from science and religion to our place in the universe.